Neoliberalism, crises and accusations of fraud: a vicious circle of reinforcing influences?. Issue 4 (11th November 2014) - Baker, Richard; Guénin-Paracini, Henri; Gendron, Yves; Morales, Jérémy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to better understand why neoliberal governance is so resilient to the crises that frequently affect all or part of the economy. Design/methodology/approach – The argument of this paper relies on a macroanalysis of discourses surrounding the Global Financial Crisis. Findings – Drawing on Girard and Foucault's work, this paper argues that the resilience of neoliberalism partly ensues from the proclivity of this mode of governing to foster, for reasons that this paper seeks to highlight, spontaneous and widespread processes of scapegoating in times of turmoil. As a consequence of these processes, crises often are collectively construed as resulting from frauds: the blame is focused on specific actors whose lack of morality is denounced, and this individualizing line of interpretation protects the regime from systemic questioning. Practical, social and political implications – Particular actors, rather than the system itself, are made accountable when things go wrong. Consequences are paramount. Today's political economy is characterized with a proclivity toward social reproduction. While substantive change is possible in theory, considerable challenges are involved in practice in overcoming the dominance of neoliberalism in society. Originality/value – Although Girard's work has exerted significant influence over a number of disciplines in the social sciences, his ideas have not yet been widely used in governance and accountability-related research. Anthropological theorizations – such as those proposed by Girard – are valuable in providing us with a sense of how power develops in the economy.